Clinical and Economic Analysis of Delayed Administration of Antithymocyte Globulin for Induction Therapy in Kidney Transplantation. (March 2013) - McGillicuddy, John W.; Taber, David J.; Pilch, Nicole A.; Kohout, Ryan K.; Bratton, Charles F.; Chavin, Kenneth D.; Baliga, Prabhakar K.
Context: The increasing number of marginal deceased kidney donors and an aging recipient population, prolonged hospitalization, and increased costs have destabilized the economic viability of kidney transplants. Objective: To determine if a delay in the administration of the day-of-discharge dose of rabbit antithymocyte globulin would result in equivalent clinical outcomes with cost savings. Design: Single-center, prospective, observational before-and-after study of adult kidney transplant recipients who received induction with rabbit antithymocyte globulin. Intervention—Patients who received a transplant between June 2006 and February 2009 and received rabbit antithymocyte globulin served as the control group. Patients who received a transplant between March 2009 and August 2010 and received rabbit antithymocyte globulin had the day-of-discharge dose delayed to the following day and administered in the clinic. A total of 231 patients (146 in the control group, 85 in the study group) were included. Baseline demographic and clinical characteristics were similar in the 2 groups. Results: Patients who had delayed administration of rabbit antithymocyte globulin had shorter stays (3.9 vs 3.1 days, P .001) and reduced inpatient costs for rabbit antithymocyte globulin (mean $860/patient); these changes were achieved without affecting acute rejection rates (5% vs 5%, P> > .99) or readmission rates. In conclusion, delayed inpatient administration of rabbit antithymocyte globulin provided identical clinical outcomes while helping to reduce inpatient costs and increase timely discharges.